Evolution of Philippine Homes with the Influence of Foreign Countries and Urbanization - Jünemann, Pauline (Journal of A Sustainable Global South, 2024)
The architectural tapestry of the Philippines, woven across its 7000 islands, reflects the indelible imprints of Spanish and American colonization. From indigenous tribal roots to the contemporary era, the nation's architectural and social landscapes have undergone profound transformations. This study explores the evolution, from humble wooden huts to modern skyscrapers, as a testament to the enduring impact of foreign nations on the Philippines' architectural identity. A critical examination is undertaken to assess the preservation of vernacular, native architecture amidst pervasive external influences, and the consequences of rapid urbanization. The inquiry centers on understanding the persistence of the indigenous spirit in a nation profoundly shaped by external forces. With a focus on the role of urbanization in shaping the lives of native populations, the study questions whether vernacular architecture can offer sustainable solutions in the context of fast-growing cities. Delving into the inherent sustainability of vernacular architecture, which inherently responds to the needs of the people, the research contributes insights into the delicate equilibrium between progress and preservation. As the Philippines stands at a crossroads amidst swift evolution and technological advancements, the imperative to balance progress with sustainable practices becomes increasingly pronounced, impacting lives and shaping the architectural identity of the nation. Index Terms — philippines, spain, urbanization, vernacular, bahaykubo, residential.